Awe the new science of everyday wonder and how it can transform your life - Keltner, Dacher (New York Penguin Press, 2023)
"From professor of psychology at U. C. Berkeley and one of the foremost experts on the science of emotions comes a groundbreaking and essential exploration into the history, science, and understanding of awe, and a guide for how we might all cultivate a deeper sense of awe and transform our lives and our world Awe, one of the most elusive emotions, is hard to pin down. How do we begin to measure the goosebumps we feel when we first see the Grand Canyon, or the utter amazement when we watch a child walk for the first time? How do you put into words the collective effervescence of standing in a crowd and singing in unison, or the wonder you feel while gazing at centuries-old works of art? Up until fifteen years ago, we didn't know how to measure awe, the feeling we get when encountering vast mysteries that transcend our understanding of the world. Scientists were studying emotions like fear and disgust, emotions that seemed essential to how the human race endures. But recently, we've come to realize that through the span of evolution, we meet our most basic needs socially. We survive thanks to our capacities to cooperate, form communities, and create culture that strengthen our sense of shared identity - actions that are sparked and spurred by awe. In AWE, Dacher Keltner, one of the leading experts on the science of emotions, presents a radical investigation and deeply personal inquiry into awe. Revealing new research into how awe transforms our brains and bodies, alongside an examination of awe across history, culture, and within his own life, Keltner shows us how awe leads us to appreciate what is most humane in our human nature. And during a moment in which our world feels more divided than ever before, we need a story of awe, an invitation to cultivate awe in our everyday life as an antidote. If we open our minds, it is awe that sharpens our reasoning and orients us towards big ideas and new insights, that cools our immune system's inflammation response and strengthens our bodies. It is awe that activates our inclination to share and create strong networks, to take actions that are good for the world around us. It is awe that transforms who we are, that inspires the creation of art, music, and religion. At turns radical and profound, brimming with enlightening and practical insights into the power of awe, AWE is both an invitation and a field guide, from not only one of the leading voices on the subject, but a fellow seeker of awe in his own right, to place awe as a vital force within our lives"--
Introduction -- Section I. A science of awe. Eight wonders of life ; Awe inside out ; Evolution of the soul -- Section II. Stories of transformative awe. Moral beauty ; Collective effervescence ; Wild awe -- Section III. Cultural archives of awe. Musical awe ; Sacred geometries ; The fundamental it -- Section IV. Living a life of awe. Life and death ; Epiphany.
Includes bibliographical references (pages 255-295) and index.
112276
Keywords: Awe; Wonder; Emotions; Psychology -- Emotions; Psychology -- Cognitive Psychology & Cognition; Biography & Autobiography -- Social Scientists & Psychologists; Self-help publications